Rekomendasi Kata Kunci Produk Variasi Motor Menggunakan Metode Analytical Hierarchy Process - Hafidz Aby Pratama; Ni Gusti Ayu Putu Harry Saptarini; Ni Ketut Pradani Gayatri Sarja (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2026)
The rising trend in motorcycle modification drives business owners to optimize digital marketing strategies through relevant product keywords. However, keyword determination is often conducted subjectively without a structured approach. This study aims to determine keyword recommendations for motorcycle variation products using the Analytical Hierarchy Process (AHP) method. The AHP method works by breaking down multi-criteria problems using pairwise comparison matrix calculations based on Relevance and Search Volume criteria. The results indicate that the AHP method is capable of determining keyword priorities objectively and systematically. The final results show that the keyword "Shockbreaker" ranks first with a score of 0,415. Consistency testing demonstrates a Consistency Ratio (CR) value of 0,00 for the criteria matrix and 0,081 for the search volume matrix. Since the CR values are CR ≤ 0,1, the weighting and decision-making results in this system successfully meet the standards established in the AHP method.